Faktor-faktor yang berhubungan dengan kejadian tuberkulosis pada anak - Donatus Dudeng, A. Roni Naning, Dibyo Pr (Berita Kedokteran Masyarakat (BKM), 2006)
Background: Still tuberculosis (TB) is the main problem for most of world society, especially in developing countries; and Indonesia is the third biggest contributor in TB prevalence after China and India It is a chronic infectious disease, which more fatal than any other infectious disease. The result of survey on domestic health in 1995 sait that tuberculosis is the third-death cause after cardiovascular and respiratory diseases upon all age groups, and is the first of any kind of infectious diseases. Out of 100,000 inhabitants, it was estimated that there are 130 cases among adults; 5-15% of them are children. From 2002 to early 2005, 448 tuberculosis cases in children had been found in Gunungkidul Regency. They were diagnosed in Health Center of Society (Puskesmas) and General Hospital of District Wonosari. Objective: The study is focused on recognizing the risk factors of tuberculosis among children. Method: This study is observational using case-control study. The 218 subjects are sufferers of tuberculosis among children diagnosed in General Hospital of District Wonosari during last-twelve months, consisting of 109 cases and 109 control group. Selected purposively using fixed disease sampling method, the subjects were taken from all cases diagnosed in last-twelve months at General Hospital of District Wonosari in Gunungkidul Regency. Data were collected by interviewing and measuring; the result analyzed by several means, viz,, univariate, bivariate, and multivariate analysis. Result: The result indicated that the risk factors of tuberculosis in children are contact history with odds ratio at 3.87 and p-value at 0 00; and nutritional status with odds ratio at 3.21 and p-value at 0.00 Conclusion: Child's contact history and nutritional status are dominant risk factors for causing tuberculosis among children, thus the two factors need to be focus of attention in programs of eradicating tuberculosis. Keywords: tuberculosis in children, risk factors, susceptibility